Impact of an exergame intervention on cognitive-motor functions and training experience in young team sports athletes: a non-randomized controlled trial - Anna Lisa Martin-Niedecken; Anna Lisa Martin-Niedecken; Valentin Bucher; Manuela Adcock; Eling D. de Bruin; Eling D. de Bruin; Eling D. de Bruin; Alexandra Schättin; Alexandra Schättin (Frontiers Media S.A., 2023)
IntroductionTeam sports athletes need excellent perceptual-cognitive skills, particularly executive functions (EF) to strategically perform on the field. The transfer effect of cognitive training might be accomplished by the inclusion of cognitive stimuli into a physically active environment as these couplings are required in real game situations. A training approach that combines both components is exergaming. The primary objective of this study was to gain preliminary insights into the effects of exergaming on cognitive-motor functions in young team sports athletes. The secondary objective was to investigate participants' training experience and well-being over time.MethodsParticipants were assigned to the intervention or control group. In the intervention group, participants trained with the ExerCube-a mixed reality exergame. The training was planned for 10 weeks (two sessions per week à 25 min) but had to be shortened by 2 weeks due to COVID-19 restrictions. The control group had no additional training. Outcomes included a computer-based alertness test and a cognitive-motor test battery to assess different EF (flexibility, divided attention, and inhibition) via a FitLight Trainer setup.ResultsTwenty-four athletes [mean age (±SD) 15.0 ± 0.7 years], evenly split into the intervention group (N = 12; male N = 6; female N = 6; 14.7 ± 0.5 years) and the control group (N = 12; male N = 7; female N = 5; 15.3 ± 0.8 years), participated in the study. Participants in the intervention group performed on average 9.4 ± 3.3 training sessions over 8 weeks. Significant time x group interaction effects were evident for the cognitive-motor sub-tests flexibility (F = 12.176, p < 0.001, d = 1.488) and divided attention for auditive stimuli (F = 9.776, p = 0.002, d = 1.404) in favour of the intervention group. For the alertness test, a medium effect size (time x group interaction) was seen for the variability of the reaction time (F = 2.196, p = 0.138, d = 0.632) in favour of the intervention group. Training experience and well-being were consistently at medium to high levels.ConclusionThe ExerCube training yielded positive effects on concentration, flexibility, and divided attention indicating that exergaming can be an innovative training approach for team sports athletes.